Influence of obesity in central blood pressure. Issue 2 (February 2015) - Pichler, Gernot; Martinez, Fernando; Vicente, Antonio; Solaz, Elena; Calaforra, Oscar; Lurbe, Empar; Redon, Josep
Abstract : Background: Obesity is an important risk factor for cardiovascular disease and has become a major concern in healthcare due to its high prevalence worldwide. The aim of the present study was to investigate the impact of BMI on central blood pressure (BP) and pulse wave velocity (PWV) in normotensive and hypertensive patients. Patients and methods: Normotensive and hypertensive adult patients who attended the outpatient clinic of cardiovascular risk were included. Peripheral BP was obtained in the brachial artery by using an oscillometric device (OMRON M-6). Central aortic BP waveform was reconstructed from the radial artery pressure waveforms (SphygmoCor, AtCor Medical, Sydney, Australia) and central BP was calculated. Carotid–femoral PWV was measured by an automatic device (Complior, Artech, France). Results: We examined a total of 351 patients [50.7% women; 77 patients normal-weight (BMI < 25 kg/m 2 )], 274 patients overweight or obese (BMI ≥25 kg/m 2 ). Central SBP showed a positive association with male sex and mean BP, but a negative association with overweight/obesity. PWV was positively associated with age, male sex, central BP, peripheral BP and BP treatment, whereas BMI of at least 25 kg/m 2 led to a decrease in PWV in patients with the same central SBP levels. Likewise, PWV was lower in the overweight/obese group compared to the normal-weight group at the same central SBP. Conclusion: Overweight and obesity tend to have lower central SBP as compared to lean patients, mainly in women. Further research is required to assess the interaction between body weight and vascular dynamics and their clinical implications.